25a 2 − 4b 2 + 28bc − 49c 2

Dear Student!

25a2 – 4b2– 28bc – 49c2

= (5a)2 – (2b)2– 28bc – (7c)2

= (5a)2 – {(2b)2 + 28bc + (7c)2

= (5a)2 – {(2b)2 + 2 × 2b × 7c + (7c)2

= (5a)2 – (2b + 7c) [(x + y)2 = x2 + 2xy + y2]

= {(5a) – (2b + 7c)} {(5a) + (2b + 7c)}   [x2y2 = (xy) (x + y)]  

= (5a – 2b – 7c) (5a + 2b + 7c)

Cheers!

  • 16

ANS:  25a2 − 4b2 + 28bc − 49c2

=> (5a+ 2b) (5a-2b) + 7c (4b- 7c)

  • 2

 25a2 − 4b2 + 28bc − 49c2

(5a)2 -(2b)2  +7(4bc-7c2)

=(5a+2b) (5a-2b) +7c(4b-c)

  • 4

 how is   x(5x-6)/3x =1/3 (5x-6)

  • 2
What are you looking for?